Lymphocyte proliferative responses in haemophiliac patients: relations to clinical and immunological findings - Aymard, J P; Janot, C; Briquel, M E; Schooneman, F; Legras, B; Alexandre, P; Streiff, F (Haematologia, 1988)
Blood lymphocyte proliferative responses to mitogens were studied in 65 patients with haemophilia (haemophilia A: 54 patients, haemophilia B: 11 patients) in parallel with 39 male control subjects. As a group, patients with haemophilia did not demonstrate abnormal proliferative responses to phytohaemagglutinin (PHA), Concanavalin A (ConA) and pokeweed mitogen (PWM) when compared with healthy controls. When the patients were analysed according to their seropositivity for antibody to human immunodeficiency virus (HIV), those who were positive had significantly decreased PHA, ConA and PWM responses. Haemophiliac patients with T4+/T8+ ratios less than 1 had reduced proliferative responses to PHA, ConA and PWM when compared to patients with ratios greater than 1. No significant difference in mitogen responses were found when the patients were analysed according to the presence or absence of palpable lymphadenopathy. Those patients with haemophilia A who had received more than 5 x 10(4) units of factor VIII during the two years preceding the study showed no significant difference in PHA, ConA and PWM responses when compared to patients receiving less.